2017
DOI: 10.1021/acs.jafc.7b02657
|View full text |Cite
|
Sign up to set email alerts
|

New Aromatic Compounds from the Fruiting Body of Sparassis crispa (Wulf.) and Their Inhibitory Activities on Proprotein Convertase Subtilisin/Kexin Type 9 mRNA Expression

Abstract: Successive chromatography of EtOAc-soluble extracts of the fruiting body of Sparassis crispa (Wulf.) resulted in isolation of four new aromatic compounds, sparoside A (1) and sparalides A-C (3-5), two new naturally occurring compounds, 2 and 6, and eight known compounds, 7-14. The chemical structures were determined by interpretation of nuclear magnetic resonance and mass spectrometry spectroscopic data. Extract, solvent-soluble fractions of the extract, and all of the pure compounds isolated from the fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In contrast, recent studies showed that the aromatic compounds isolated from S . crispa are effective for the treatment of cancer 38 or hyperlipidemia 39 . Here, we used the mycelium of S .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies showed that the aromatic compounds isolated from S . crispa are effective for the treatment of cancer 38 or hyperlipidemia 39 . Here, we used the mycelium of S .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SC contains various bioactive compounds, such as methyl orsellinate, xanthoangelol, 4-hydroxyderricin, sparoside A, hanabiratakelide A, adenosine, and 5α,6α-epoxy-22E,24R -ergosta-8 14 ,22diene-3b,7b-diol 15,37 . Table 5 summarizes a subset of these bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of valuable edible mushroom, S. crispa shows various medicinal properties, such as anti-tumor [1], anti-inflammation [2], immunoregulation [3], hypoglycemic effect [4], and ameliorating skin conditions [5]. A number of previous studies have reported the isolation and structural determination of more than thirty compounds within different categories in this species, including alkaloids [6], phthalides [6,7], sesquiterpenes [8], steroids [9], and other compounds [10]. The genes responsible for the synthesis of these secondary metabolites were known to form clusters.…”
Section: Introductionmentioning
confidence: 99%